Using Humor to Promote Social Distancing on Tiktok During the COVID-19 Pandemic - Xiao, Yi; Yu, Shubin (Frontiers in Psychology, 2022)
Background: During the COVID-19 pandemic, many humorous videos on how to practice social distancing appeared on social media. However, the effect of using humor as a crisis communication strategy to persuade people to conform to social distancing rules is not known. Objective: Drawing on the literature on humorous message framing and crisis communication, this research explores the effectiveness of a humorous message in communicating social distancing rules in two crisis severity phases (low vs. high severity), and also evaluates how humor affects individuals’ online and offline engagement intentions during the COVID-19 pandemic. Methods: A 2 (message framing: humorous vs. non-humorous) x 2 (crisis severity phase: low vs. high) between-subjects design experiment was conducted to test the research questions during the first weeks of the COVID-19 pandemic in China from January 30 to February 2, 2020. Results: The results showed that the severity of the phase of a health crisis can significantly affect stakeholders’ online and offline responses towards the disease. More specifically, in a low severity phase, humor led to increased source likability and higher online engagement intentions. Whereas, in a high severity crisis phase, humor led to a decrease in perceived risk and reduced individuals’ offline engagement intentions. Conclusions: Humor can motivate both more online engagement and offline protective action intention when the crisis severity phase is low, while when crisis severity soars, a non-humorous message should be more desirable. More specifically, using humor in communicating information about an infectious disease can enhance the spokesperson’s likeability in a low severity phase, which may help to spread health information to a larger audience and triggers more protective actions. While, the negative side of using humor in communicating an infectious disease appears in severe crisis phases, as it then decreased the public’s perception of risk and also reduced offline engagement intention. Going beyond previous research, this study recognized that crisis severity changes in different phases of the spread of infectious disease, thereby providing actionable strategy selections for crisis practitioners in a dynamic communication environment.